2017
DOI: 10.1136/bmjgh-2017-000462
|View full text |Cite
|
Sign up to set email alerts
|

‘We lost because of his drunkenness’: the social processes linking alcohol use to self-harm in the context of daily life stress in marriages and intimate relationships in rural Sri Lanka

Abstract: IntroductionHarmful alcohol use has been found to cause detriment to the consumers and those around them. Research carried out in Sri Lanka has described the socioeconomic consequences to families owing to alcohol consumption. However, the social processes around alcohol use and how it could result in behaviour such as self-harm was unclear. With an outset in daily life stressors in marriages and intimate relationships we explored alcohol use in families with a recent case of self-harm.MethodsQualitative data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 31 publications
3
52
0
Order By: Relevance
“…The risk of attempted suicide is nearly double in women living in households with a household member who misuses alcohol after controlling for socio-economic variables. This is consistent with previous work from India which has indicated that increased levels of hazardous drinking in male household members increases the risk suicidal behaviour in co-habiting women ( Gupta et al, 2015 ), and research from Sri Lanka indicating husband/father alcohol misuse as a preceding factor for suicidal behaviour ( Gamburd, 2008 , Konradsen et al, 2006 , Marecek, 2006 ; Sørensen et al, 2017 ) Problematic alcohol use is often associated with intimate partner violence in Sri Lanka ( Abeyasinghe, 2002 , Gamburd, 2008 ). It may be that the increased risk of attempted suicide seen in women in households with problem alcohol use is due to these women experiencing such violence.…”
Section: Discussionsupporting
confidence: 89%
“…The risk of attempted suicide is nearly double in women living in households with a household member who misuses alcohol after controlling for socio-economic variables. This is consistent with previous work from India which has indicated that increased levels of hazardous drinking in male household members increases the risk suicidal behaviour in co-habiting women ( Gupta et al, 2015 ), and research from Sri Lanka indicating husband/father alcohol misuse as a preceding factor for suicidal behaviour ( Gamburd, 2008 , Konradsen et al, 2006 , Marecek, 2006 ; Sørensen et al, 2017 ) Problematic alcohol use is often associated with intimate partner violence in Sri Lanka ( Abeyasinghe, 2002 , Gamburd, 2008 ). It may be that the increased risk of attempted suicide seen in women in households with problem alcohol use is due to these women experiencing such violence.…”
Section: Discussionsupporting
confidence: 89%
“…Silence accompanied with the body language described above can, in the Sri Lankan context, be a way for women to live up to the gendered ideal of women silently 'bearing up under their problems'. This behaviour has been pointed out in other studies (Ruwanpura 2006;Sørensen et al 2017). It is also inherent in the norm of lajja-baya, which demonstrates that silence may be perceived as a way of positioning oneself as respectable.…”
Section: Participantsupporting
confidence: 73%
“…When carrying out formal observations to understand how, where and with whom alcohol was consumed, the first author was accompanied by a research assistant. Observations took place in villages at legal and illegal alcohol selling establishments and in households during interviews carried out for the purpose of another study (Sørensen et al, 2017 ). Observations were also made at social gatherings, such as funerals and weddings.…”
Section: Methodsmentioning
confidence: 99%
“…Despite these initiatives, alcohol consumption continues to have negative consequences for Sri Lankans, including in relation to poverty (Baklien & Samarasinghe, 2004 ), domestic violence (Subramaniam & Sivayogan, 2001 ), depression (Ariyasinghe, Abeysinghe, Siriwardhana, & Dassanayake, 2015 ), unintentional injuries in children (Punyadasa & Samarakkody, 2016 ), traffic accidents (Edirisinghe, Kitulwatte, & Senarathne, 2015 ) and self-harm (Pearson et al, 2014 ; Sørensen et al, 2017 ). The rate of cirrhosis is among the highest in the world (Abeyasinghe, 2011 ).…”
Section: Introductionmentioning
confidence: 99%